PERKEMBANGAN PERUSAHAAN DAERAH AIR MINUM (PDAM)TIRTA DHARMA KOTA SOLOK TAHUN 1984-2020 - Zafira Marshanda; Zul Asri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research is a historical study that discusses the development of PDAM (Regional Water Company) Tirta Dharma Solok City in 1984-2020. The problem that the author raises is regarding the development of PDAM Tirta Dharma from year to year according to the era of its leadership. This type of research includes qualitative research with historical research methods. In this historical research, there are several steps, namely heuristics (collecting data), source criticism (conducting criticism of existing sources), interpretation (conducting interpretations related to historical facts) and historiography (writing history). In 1982 the Solok City Regional Drinking Water Company was formed as a BUMD (Regional Owned Enterprise) of the Solok City government. Full management by the government of Solok City has been carried out since 1984. The results of the study show that the development of PDAM Tirta Dharma, Solok City has increased every year. Developments in the clean water infrastructure sector, clean water production, and the scope of clean water services. The Regional Drinking Water Company (PDAM) Tirta Dharma, Solok City, is still experiencing problems in management. Constraints such as distribution pipe leaks, not yet optimal service coverage.Keywords: PDAM Solok City, Development, Management